SDHP (School Dental Health Programs) at Public Health Semarang - Sadimin Sadimin; Sariyem Sariyem; Sulur Joyo Sukendro (Poltekkes Kemenkes Semarang, 2013)
The aim of this study was to evaluate the implementation of programs in health centers SDHP working area of Semarang City Health Office. This type of research is a qualitative research method of observation and in-depth interviews. Key informants are seven dental nurses, eight and seven informant informant triangulation supporting parents. Results showed in general for most public workers has only two executive power SDHP program. Availability of funds for the program in the clinic SDHP Jamkesmas sourced from funds, operating funds have not been allocated to the program UKS / SDHP. Strategies that do not SDHP focused on promotive and preventive efforts but networking and referral. SDHP program targets the majority of class I crawl. Criteria SDHP held that SDHP Integration and selective. Implementation was carried out together with the BIAS program.